2019
DOI: 10.1111/pan.13725
|View full text |Cite
|
Sign up to set email alerts
|

Real fasting times and incidence of pulmonary aspiration in children: Results of a German prospective multicenter observational study

Abstract: Background Prolonged fasting before anesthesia is still common in children. Shortened fasting times may improve the metabolic and hemodynamic condition during induction of anesthesia and the perioperative experience for parents and children and simplify perioperative management. As a consequence, some centers in Germany have reduced fasting requirements, but the national guidelines are still unchanged. Aims This prospective multicenter observational study was initiated by the Scientific Working Group for Pedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 13 publications
(30 reference statements)
2
20
0
4
Order By: Relevance
“…There is a lack of studies evaluating the association between real fasting times and the incidence of pulmonary aspiration, and the primary sample size (n = 3000) in our national audit was too low for a subgroup analysis 1 . Therefore, this study was extended, and after inclusion of more than 12 000 cases, we found no association between clear fluid fasting times and adverse events (regurgitation or pulmonary aspiration) during anesthesia and no change in adverse events in the group with clear fluid fasting times between 1 and 2 hours compared to longer fasting times 15 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…There is a lack of studies evaluating the association between real fasting times and the incidence of pulmonary aspiration, and the primary sample size (n = 3000) in our national audit was too low for a subgroup analysis 1 . Therefore, this study was extended, and after inclusion of more than 12 000 cases, we found no association between clear fluid fasting times and adverse events (regurgitation or pulmonary aspiration) during anesthesia and no change in adverse events in the group with clear fluid fasting times between 1 and 2 hours compared to longer fasting times 15 .…”
Section: Discussionmentioning
confidence: 98%
“…A recent national audit evaluating real fasting times showed that prolonged fasting was still common in pediatric anesthesia in Germany and that improvements of national fasting guidelines are urgently needed 1 . As a consequence and based on studies in volunteer healthy unstressed children using magnetic resonance imaging or ultrasound, many clinics have changed their local regimens toward a more liberal clear fluid fasting policy, but it has been hotly contested whether the national fasting guidelines should be revised.…”
Section: Introductionmentioning
confidence: 99%
“…A recent national audit of real fasting times including 3324 children showed not only that prolonged fasting is still common in Germany, but also that real fasting times for clear fluids and light meals were frequently shorter than recommended in current guidelines 1 . This was due to the fact that some of the participating centers promoted liberal fasting, whereas others were more conservative in order to avoid legal uncertainties.…”
Section: Introductionmentioning
confidence: 99%
“…The meta-analysis of 8 studies published between 1998 and 2019 with a total sample size of 4, 26 594 patients yielded an incidence of 49/1,00,000 aspirations in children with a 95% CI of 30/1,00,000 to 81/1,00,000 (LOE–High). [ 224 225 226 227 228 229 230 231 ] The Anaesthetic Incident Monitoring Study reported 133 cases of aspiration in children <14 years out of the total 240 incidents of aspiration. Only 17 of these children were inadequately fasted (LOE – Very Low).…”
Section: Paediatric Sectionmentioning
confidence: 99%
“…Observational studies and surveys found the duration of preoperative fasting is prolonged in 60-70% of the children posted for surgery (LOE – Very Low). [ 229 270 271 272 ] In a study comprising of 1350 children (2-16 years) with a median fasting time of 12.05 hours, 56% were found to be very hungry or starving, while 27% of the children were very thirsty (LOE – Very Low). [ 273 ] Children <36 months showed higher concentration of plasma ketone bodies and lower mean arterial pressure immediately after anaesthetic induction following prolonged duration of fasting.…”
Section: Paediatric Sectionmentioning
confidence: 99%